Effects of Meditation With Music on Concentration of School Students of Gwalior: The Impact of Flute and Piano Meditation on Concentration of School Students in Gwalior (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The purpose of the study was to determine the effects ofmeditation with flute and piano on Concentration level. 20 students agedbetween 15-17 years were selected randomly for each group of flute, piano andcontrol group from class viii and ix of Pragati Vidya Pheeth School. MirrorDrawing Test was used to assess the concentration level of the students.Analysis of co-variance was used for statistical analysis of the data. Resultsrevealed that there is a significant difference between flute and piano musicmeditation on concentration level, whereas there is no significant differencewith both the groups with control group.